2001
DOI: 10.1101/gr.gr-1531rr
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Role of Restriction/Modification Systems as Revealed by Comparative Genome Analysis

Abstract: Type II restriction modification systems (RMSs) have been regarded either as defense tools or as molecular parasites of bacteria. We extensively analyzed their evolutionary role from the study of their impact in the complete genomes of 26 bacteria and 35 phages in terms of palindrome avoidance. This analysis reveals that palindrome avoidance is not universally spread among bacterial species and that it does not correlate with taxonomic proximity. Palindrome avoidance is also not universal among bacteriophage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 43 publications
2
76
0
Order By: Relevance
“…This strategy also protects host bacteria from attack by its own REase. Interestingly, palindrome avoidance is observed to a greater extent in bacteria than in phages (84). Palindrome/restriction site avoidance by mutations, however, may affect other cellular functions.…”
Section: Fitness Cost Incurred By R-m Systems On Host Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy also protects host bacteria from attack by its own REase. Interestingly, palindrome avoidance is observed to a greater extent in bacteria than in phages (84). Palindrome/restriction site avoidance by mutations, however, may affect other cellular functions.…”
Section: Fitness Cost Incurred By R-m Systems On Host Bacteriamentioning
confidence: 99%
“…(i) It has been observed that bacteria containing an R-M system have a decreased restriction site frequency in the genome for that particular recognition sequence, a phenomenon called restriction site avoidance (84). This strategy is employed by phages to evade restriction (see "Strategies against R-M Systems").…”
Section: Fitness Cost Incurred By R-m Systems On Host Bacteriamentioning
confidence: 99%
“…So far, we cannot find any previous report of underrepresentation of short palindromes in RNA viruses with eukaryotic hosts. However, avoidance of short palindromes in some bacterial and phage DNA genomes has been reported in several studies (Karlin et al 1992;Merkl and Fritz 1996;Rocha et al 1998Rocha et al , 2001, among others). The phenomenon is generally explained in relation to the defense mechanisms of the bacterial and phage genomes, protecting themselves against being destroyed by restriction enzymes capable of cutting up DNA molecules at certain palindromic sites.…”
Section: Discussionmentioning
confidence: 99%
“…Various statistical assessments of unusual abundance and rarity of individual words, including individual palindromes, in nucleotide sequences have been done using randomsequence models in a number of previous studies (Karlin et al 1992;Merkl and Fritz 1996;Rocha et al 1998Rocha et al , 2001Schbath et al 1995, to name just a few). The present study, however, aims at investigating the unusual abundance and rarity of palindromes collectively rather than individually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation